Applying Fracture Mechanics and Weibull Analysis to Enhance T2052 Reliability - Toderas, Mihaela; Radu, Sorin Mihai; Vilceanu, Florin; Dinescu, Stela; Ciprian, Danciu (Scientific Research, New Technologies and Applications Vol. 8, 2024)
This research provides a detailed analysis of crack propagation and fatigue in the T2052 coal mining/dumping machine. By employing fracture mechanics and Weibull analysis, a practical method for estimating component lifespan and optimizing maintenance was developed. Undetected cracks pose a significant challenge to mining equipment maintenance. To address this, we conducted static fracture analyses and modelled crack propagation based on material properties, stress intensity factors, and environmental conditions. Weibull analysis was used to characterize material variability. Our results indicate rapid crack propagation after reaching a critical length and relatively low variability in the mechanical properties of the OL52 material. Material properties and operating conditions significantly influence crack propagation rates. By modelling crack propagation, we can optimize preventive maintenance planning, thereby increasing equipment reliability and reducing costs. By identifying critical components and monitoring crack evolution, we can prevent catastrophic failures. This research demonstrates the effectiveness of fracture mechanics and Weibull analysis in assessing crack propagation and predicting component lifetime in T2052 coal mining/dumping machines. Mining operators can use these results to improve equipment reliability, reduce maintenance costs, and optimize operational efficiency. Future research could focus on refining the models used and exploring additional factors that may influence crack propagation.